The Effect of Work Discipline and Motivation on Employee Performance (at PT. Bank Mandiri Ciledug Branch) - Priehadi Dhasa Eka (Universitas Negeri Makassar, 2018)
Human resources are one of the factors directly involved in carrying out company activities. This study aims to determine the effect of work discipline and motivation on employee performance at PT. Bank Mandiri Ciledug Branch. The method used in this research is descriptive method with an associative approach with proportional random sampling technique. Methods of data analysis using descriptive and verification with regression analysis, determination, and hypothesis testing partially or simultaneously. The results showed that partially the independent variables affect the dependent variable. Simultaneously testing the influence also concluded work discipline, and motivation had a positive and significant effect on employee performance with an influence contribution of 41.1%. Hypothesis testing obtained a probability statistic value <0.05 thus H0 is rejected and H1 is accepted.